Days of the knights: a tale of castles and battles - Maynard, Christopher (New York: DK Pub., 1998)
Presents a day in the life of a medieval lord as he runs the land over which he holds power.
"Grades 2-4."
Keywords: Knights and knighthood. -- Juvenile literature; Civilization, Medieval. -- Juvenile literature; Knights and knighthood; Civilization, Medieval